Analyzing banking risk : a framework for assessing corporate governance and risk management - Greuning, Hennie van (Washington, D.C : World Bank, 2020)
Provides a comprehensive overview of topics focusing on assessment, analysis, and management of financial risks in banking. The publication emphasizes risk management principles and stresses that key players in the corporate governance process are accountable for managing the different dimensions of financial and other risks. This fourth edition remains faithful to the objectives of the original publication. The new business aspects affecting banking risks, such as mobile banking, and regulatory changes over the past decade-- specifically those related to Basel III capital adequacy concepts-- have been included, as have new operational risk management topics, such as cybercrime, money laundering, and outsourcing. This publication will be of interest to a wide body of users of bank financial data. The target audience includes the persons responsible for the analysis of banks and for the senior management or organizations directing their efforts.
Overview of banking risks -- A framework for risk analysis -- Corporate governance -- Balance sheet structure -- Income statement structure -- Capital adequacy -- Credit risk management -- Liquidity risk management -- Managing liquidity and other investment portfolios -- Market risk management -- Currency risk management -- Asset-liability management -- Operational risk management in a treasury environment -- Transparency and data quality -- A risk-based approach to bank supervision.
Keywords: BANK MANAGEMENT